2010
DOI: 10.1016/j.transci.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel and unexpected clearance mechanisms for cold platelets

Abstract: Storage at room temperature is limited to 5 days because of the risk of bacterial growth and loss of platelet functionality. Platelet refrigeration remains impossible, because once chilled, platelets are rapidly removed from circulation. Chilling platelets (<4 h) clusters glycoprotein (GP) Ibα receptors, and β2 integrins on hepatic macrophages recognize clustered βGlcNAc residues leading to rapid clearance of acutely chilled platelets. Prolonged refrigeration increases the exposure of galactose residues such t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 72 publications
3
65
0
1
Order By: Relevance
“…Murphy and Gardner [17] reported that the immediate circulatory recovery and survival half-life of radioactive platelets after 18 h of room-temperature storage were similar to those of fresh platelets (at 55% and 4.0 days, respectively), whereas the recovery decreased to 40% with a survival half-life of only 1.3 days after 18 h of storage at 4°C. Platelet chilling induces rapid irreversible disk-to-sphere shape changes [18]. In the current study, the BDNF levels in the samples increased over a period of 6 h even when the plasma was stored at room temperature.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Murphy and Gardner [17] reported that the immediate circulatory recovery and survival half-life of radioactive platelets after 18 h of room-temperature storage were similar to those of fresh platelets (at 55% and 4.0 days, respectively), whereas the recovery decreased to 40% with a survival half-life of only 1.3 days after 18 h of storage at 4°C. Platelet chilling induces rapid irreversible disk-to-sphere shape changes [18]. In the current study, the BDNF levels in the samples increased over a period of 6 h even when the plasma was stored at room temperature.…”
Section: Discussionmentioning
confidence: 53%
“…Platelets are metabolically active during storage at room temperature, which contributes to continuously diminished platelet function. Furthermore, metabolic products (e.g., lactate) accumulate during room-temperature storage and lead to an increase in acidity, and pH levels below 6.0-6.2 have been associated with severely diminished platelet viability [18]. …”
Section: Discussionmentioning
confidence: 99%
“…54,55 Recently, loss of sialic acid has been identified as a determinant for the removal of senescent circulating platelets. 56 Sialic acid loss is likely mediated by upregulation of platelet sialidases, ie, Neu1 and Neu3, expressed in granular compartments and on the plasma membrane, respectively.…”
Section: Senescence-induced Platelet Clearance By the Amrmentioning
confidence: 99%
“…We also demonstrated that isolated fresh platelets have receptors bearing terminal ␤-galactose, supporting the notion that sialic acid is removed from the platelet surface during circulation. 30 Preferential cleavage of desialylated platelet VWFR, therefore, might preserve some hemostatic function in the platelets. Rapid removal, in this case, would also place a higher burden on the replenishment system.…”
Section: Platelet Refrigeration Induces Mp-mediated Gpib␣ and Gpv Shementioning
confidence: 99%